Penerapan Konsep Arsitektur Ekologis Pada Redesain Tempat Pelelangan Ikan Di Kota Tegal - Aris Mulyono; Sri Yuliani; Samsudi Samsudi (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2018)
Indonesia as an archipelago country is very potential to develop the fishery economy. Tegal Fish Trading Market is one of facility to support fishery economic activities in Indonesia which has various problems. Redesign of Tegal Fish Trading Market with Eco-Architecture as a design strategy, expecting  to solve and overcome the existing problems of the building and the area. With building evaluation, we know the problems that exist in the establishment of the Building. Then ecological principles selected to solve the problems that exist. Based on the results of identification, the ecological aspects that will be implemented is nature conservation, especially the beach and coastal, sustainable utility planning that focused on waste treatment and sanitation system, structural planning, facade, building appearance and ecological material so this building could survive in long term (sustainable). By redesign, this Fish Trading Market can be better planne, and then it will have more attractive view of buildings, planned waste treatment systems and planned sanitation systems, and also can recover the nature.